THE MODELING OF PARTICLE SIZE DISTRIBUTION DEPENDENCY WHEN MILLING MAGNETIC POWDER USING BEATER MILL - Yu. M. VERNIGOROV; I.N. EGOROV; S.I. EGOROVA (Advanced Engineering Research, 2007)
The model that allows forecasting of particle size distribution when milling magnetic powder in the magnetovibrating layer using beater mill was proposed. Model arguments are initial grain size distribution, milling time and variable magnetic field gradient. The correlation of model with experimental results is shown.